CHRONIC OBSTRUCTIVE PULMONARY DISEASE, DIAGNOSIS AND TREATMENT - Wijaya Putra, IGN Paramartha; Made Artika, I Dewa (E-Jurnal Medika Udayana; vol 2 no1 (2013):e-jurnal medika udayana, 2013)
Chronic obstructive pulmonary disease (COPD) is one of a group non communicable diseases that public health has been an issues in Indonesia. At the 2007 in United State, COPD is the third leading cause of death. Smoking habit is a major cause COPD. Symptoms and sign were generally nonspecific. The provision of therapy that late can provide the impact of death. Spyrometry needed for clinical diagnosis COPD. Comparison FEV 1 /FVC <0,70 after bronchodilator medication can diagnose COPD. Bronchodilator medication is a first line treatment for COPD. Any medicine must specific against each patient, because symptoms and severity of limitations air flow affected by many factors.
Keywords: chronic obstructive pulmonary disease, respiratory disease, bronchodilator